Gendered narratives and cultural shifts: A qualitative study on decadal changes in community alcohol consumption - Tan, Ming Gui; Walton Wider; Pang, Nicholas Tze Ping; Helen Benedict Lasimbang; Wendy Diana Shoesmith; Corine Rosapane M. Tangau; Leilei Jiang; Natchana Bhutasang (Public Library Science, 2024)
Alcohol consumption has been a central practice in Sabah, Malaysia. However, this region has witnessed a nuanced shift in drinking habits over the last decade, raising concerns about the health, economic, and social implications of alcohol use within the community in Sabah. This study explores the impact of gender narratives and cultural transformations on alcohol consumption within Sabah over the last decade. The objectives of this research include 1) assessing the shifts in alcohol consumption patterns over the last 10 years, 2) understand the role of gender differences in shaping these patterns, and 3) identify the economic consequences resulting from the changes. Employing a qualitative approach, we conducted focus group interviews with members of the native community, each group consisting of up to 7 participants. Thematic analysis was used to identify key themes pertaining to gender roles, cultural practices, and socioeconomic influences of alcohol consumption. The data were then contextualized using Bronfenbrenner’s social-ecological model and social role theory. The study reveals a significant shift in drinking habits. Historically, alcohol was mostly consumed by men, but now more women are drinking, changing long-standing gender roles related to alcohol use. Children often copy their parents’ drinking behaviors, and with alcohol being more easily available, more people are drinking than before. Our findings also expose the complex consequences of alcohol use, which extend to health concerns, familial tension, and economic hardship. Despite the entrenched cultural status of alcohol, these negative outcomes are exacerbated by a lack of supportive healthcare services. In light of these insights, the study suggests the need for intervention plans that respect the cultural background of Sabah and account for gender dynamics while tackling the current issues of alcohol misuse. The research adds to the wider conversation about managing alcohol in different cultural settings and also recommended strategies based on the findings, such as cultural and gender sensitive community programs, youth centered programs, community-based healthcare services, employment support and training and development of laws and policies.